WHEN THE STUDENTS TEACH THE PROFESSORS: LESSONS LEARNED FROM TEACHING AN ELECTIVE SEMINAR IN MULTICULTURAL LAWYERING - Mable Martin-Scott; Kimberly O'Leary (Washington University Journal of Law and Policy, 2024)
This essay is a professors’ compilation of reflections, experiences, lessons learned through their development of an upper-level elective seminar in Multicultural Lawyering at Western Michigan University Thomas M. Cooley School of Law. The WMU-Cooley Law seminar in Multicultural Lawyering allows law students the rare experiences of exploring societal perceptions of the law through engaging with racially and ethnically diverse communities while challenging students to introspectively assess and utilize their own cultural lens. With the goal of creating a more inclusive legal profession and practice, the professors find that it is the students who are teaching them how to develop legal curriculum that is respectful, challenging, honest, and empowering. With the aim of offering their lessons for adoption by other legal institutions, the professors conclude that components of respectful discourse of student experience, a high degree of student agency, and intercultural communication are the linchpins for creating an improved, diverse legal system.
Keywords: Reflections; Multicultural Lawyering; Discourse